2019
DOI: 10.1093/cdn/nzz052.p14-017-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eggs and Egg Components on Cognitive Performance, Glycemic Response, and Subjective Appetite in Children Aged 9–14 Years (P14-017-19)

Abstract: Objectives Childhood is a critical time for regular intake of high-quality nutrients to aid developing brains. Dietary protein and fat independently and additively enhance cognitive performance in adults, however there are limited studies in children. The objective of this study was to determine the effects of whole eggs and its components (egg whites [protein-rich, fat-free] vs. egg yolks [containing protein and essential fatty acids]) on cognitive performance, glycemic response, and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although most studies on egg consumption have focused on cardiovascular health, research is beginning to implicate eggs in their relationship to cognitive health (14)(15)(16)(17) , yet evidence on the benefit of whole egg consumption is lacking. A case-control study of elderly individuals in China revealed that healthy controls had higher egg intake compared with those with mild cognitive impairment, suggesting that sufficient egg intake may play a role in preventing the development of mild cognitive impairment (15) .…”
mentioning
confidence: 99%
“…Although most studies on egg consumption have focused on cardiovascular health, research is beginning to implicate eggs in their relationship to cognitive health (14)(15)(16)(17) , yet evidence on the benefit of whole egg consumption is lacking. A case-control study of elderly individuals in China revealed that healthy controls had higher egg intake compared with those with mild cognitive impairment, suggesting that sufficient egg intake may play a role in preventing the development of mild cognitive impairment (15) .…”
mentioning
confidence: 99%